Determinan Kinerja Keuangan Perbankan Syariah di Indonesia dalam Perspektif Islam - Amrizal; Isnaldi Muhammad Dini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research aims to test and analyze the influence of the variables Operational Costs, Operational Income, and Financial Deposit Ratio on Non-Performance Financing. To test and analyze Operational Costs and Operational Income and Financial Deposit Ratio to Return on Assets directly or through the Non-Performance Financing variable as a moderating variable. The research object is Islamic banks in Indonesia using secondary data from financial reports from 2017 to 2021. The research design is a quantitative analysis using path analysis. The research results prove that the variables Operational Costs, Operational Income, and Financial Deposit Ratio have a significant positive effect on the Non-Performance Financing variable, the magnitude of the influence is 32.8%. The variables Operational Costs, Operational Income, and Financial Deposit Ratio are proven to have a positive and significant influence on the Return On Assets variable, with the magnitude of the influence being 76%. Based on path analysis, the Operational Cost variable does not affect the On Assets return variable with the Non Performance Finance variable as a moderating variable. Meanwhile, the Financial Deposit Ratio variable influences the return on assets variable with the Non-Performance Finance variable as a moderating variable. Keyword: Financing Ratio, Financial Performance, Financial Report